Water temperatures of the Danube and Tisza Rivers in Hungary - Lovász, György (Hungarian Geographical Bulletin, 2012)
Based on a 60-year long hydrological observation series from the Hungarian Hydrological Service (between 1951 and 2010), the monthly mean water temperatures of both largest rivers in the Carpathian Basin, the Danube and the Tisza, important for a range of practical considerations, are studied. The monthly extremes in water temperatures are explained by the different climatic conditions in the drainage basins of the rivers: the Danube basin upstream its entrance to Hungarian territory with a marked Atlantic and the Tisza basin with a strong continental character. Changes are followed along the Hungarian stream sections. Trends in water temperature change are established and interpretations are sought with consideration to the climate change trends predicted by climatologists for Hungary. The trends are more clearly manifested for the Danube catchment than for the Tisza catchment. Within the outlined overall trends, positive and negative singularities are also identified for the coldest and hottest months and their occurrence is also analysed in regional contrast.